Lack of Diversity: Are you part of the problem or its solution? - Moro, Mirella M. (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2022: Anais do II Simpósio Brasileiro de Educação em Computação, 2022)
Do Computing courses properly prepare students for dealing with diversity, equity and inclusion? This essay delves into such a question by presenting a survey taken by Computing educators, and discussing issues, solutions and challenges within different Computing areas. It is also a call to action, because when dealing with such matters, there is no being on the fence: a person is either part of the problem or working towards its solution.